Active noise cancellation - Rahman, Fabliha; Rakesh, Kallol Sarkar; Mou, Jarin Tasin; Bhuiyan, Mohimin Al (Brac University, 2022)
This design report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2022.